Use of Patient-Reported Outcome Measures in Lower Extremity Research - Yongni Zhang; Yaning Zang; Jiayi Ren; Wenhao Guo; Ashley Disantis; Siyu Liu; RobRoy L Martin (International Journal of Sports Physical Therapy)
# Background